Computational Methods and Experimental Measurements XVIII 2017
DOI: 10.2495/cmem170101
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Convective Cooling of Cryogenic Fluids Towards Superconducting Applications

Abstract: To understand the cooling aspect through natural convection in a cryogenic fluid interacting with a constant heat source, numerical simulations are carried out in a parallelepiped enclosure. The 3D form of N-S equations is solved to obtain the detailed flow features through path line profiles, isotherm contours and velocity vectors. The effect of heater aspect ratio (x/L) on the rate of heat transfer is studied in terms of the average Nusselt number (Nuave). The results indicate that effective heat transfer en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Towards this, buoyancy driven flow in an enclosed cavity [25] forms a good test case for the present validation. This particular benchmark analysis was successfully investigated in our earlier studies in a 2D geometry [18].…”
Section: Benchmark Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this, buoyancy driven flow in an enclosed cavity [25] forms a good test case for the present validation. This particular benchmark analysis was successfully investigated in our earlier studies in a 2D geometry [18].…”
Section: Benchmark Validationmentioning
confidence: 99%
“…Prior to the present work, we have recently studied numerically the convective flow induced by a heater immersed in a 10 cst silicone oil [18]. It was shown that the characteristics of the flow depend on the length of the heater and that longer heaters lead to lower average Nusselt numbers thereby extending the predictions of [13] to the geometry of an immersed heater.…”
Section: Introductionmentioning
confidence: 99%